Case report: Adolescent breast hypertrophy with a tendency toward phyllodes tumor formation: first reported case in China - Liao, Ruiheng; Xiao, Yang; Chang, Yujing; Zhang, Zhang; Zhang, Yange (Frontiers in Oncology, 2025)
Adolescent breast hypertrophy is a rare and persistent condition that affects peripubertal females both physiologically and psychologically. We present a case of a 14-year-old patient with bilateral giant breast enlargement who underwent a successful reduction mammoplasty of 16.5% Body Weight. The right breast exhibited focal interstitial proliferation myofibroblasts, suggesting a potential risk for phyllodes tumor development. This finding represents a novel histopathological association, unreported in the literature and first documented in China.